The Bahamas Climate resilient agriculture : policies, strategies, and actions - Dormer, Dianne (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The AgREADY aims to identify and develop financeable projects aligned with regional and national priorities of Caribbean countries experiencing extreme weather events like hurricanes, which cause significant damage to the region's socio-economic fabric, particularly the agricultural sector. As agriculture represents 23% of employment in the region, vulnerability to climate impacts is a growing concern. Therefore, the project's objective is to enhance climate action in the agricultural sector by strengthening policies, frameworks, and institutional arrangements for data collection, monitoring, measuring, reporting, verifying, and analyzing agricultural activity.